Evidence on the importance of gut microbiota for the immune system - Juwalita Surapsari; Molly Dumakuri Oktarina; Tonny Sundjaya; Erika Wasito (Indonesian Nutrition Association, 2023)
Vital to the health of the host is maintaining a delicate balance in the immune system by eliminating harmful pathogens while preserving self-tolerance to prevent autoimmunity. By regulating immune homeostasis, the gut microbiota in the gastrointestinal tract provides vital health benefits to its host. It has been demonstrated conclusively that dysbiosis of these gut microbial communities can cause immune dysregulation and autoimmunity. We attempt to examine the relationship between the gut microbiota and the regulation of the innate and adaptive immune homeostasis, which can influence the development of certain disease. This literature review of recently published research and newly discovered scientific information is intended to increase awareness of the importance of maintaining a microbiota balance in the gut for immune health of the host.